Guia didático-metodológico para aprendizagem e memorização dos conhecimentos disseminados nos moocs – Massive Open Online Courses - Moreira, Elvio dos Santos (2016)
The present research has character exploratory, bibliographic and qualitative. It is based in consolidated scientific arguments in cognitive theories inspired in constructivist method and, under this perspective proposes to develop a didactic guide oriented to students of courses MOOCs - Massive Open Online Courses that will make it possible to maximize the utilization and the assimilation of the knowledge available in these courses. Intends also prepare these students in practice of a methodology of storage that enables the knowledge acquired are not lost nor be forgotten over the course of time. The theoretical framework, based on the theories of Meaningful Learning (Ausubel), the Genetic Epistemology (Piaget), Socioconstructivist (Vigotsky) and the Multimedia Learning (Mayer), subsidizes the understanding of important concepts such as meaningful learning, previous knowledge, and conceptual maps. Supported by fundamental contribution of the Theory of Categories, which are inter-related to concepts applicable to teaching methodology supported by use of structured knowledge maps in the establishment of the binomial teaching-learning; and with valuable study performed by teachers Luciano Lima (UFU) and Rubens Barbosa Filho (UEMS) that culminated with the development of Exponential Effective Memorization Method in Binary Base (Double MEB).